Computerized tomography findings of neutropenic enterocolitis and its relationship with prognosis - Ali Mahir Gündüz; Nurşen Toprak (Van Tıp Dergisi, 2021)
INTRODUCTION: Neutropenic Enterocolitis (NE) is a serious complication characterized by transmural inflammation of the large and small intestines, with especially the cecum. The diagnosis of NE is usually based on a combination of clinical and radiological findings, and the most reliable method in diagnosis is computed tomography (CT). In this study, we wanted to investigate which intestinal segments are affected in 15 patients we diagnose NE with CT and whether there is a relationship between intestinal involvement and prognosis. METHODS: After the CTs of all patients were examined in detail, they were divided into groups according to the intestinal segments held. Then, by measuring the size of the intestinal wall where it is the thickest, it was investigated whether there is a relationship between intestinal involvement and prognosis. RESULTS: We detected an increase in mucosal enhancement and wall thicknesses of at least 11 mm in the terminal ileum and other intestinal segments, primarily in the cecum and the ascending colon. The mesentery adjacent to the thickened intestinal segments had inflammatory contamination-heterogeneity and secondary mesenteric stranding, some local lymphadenopathies (LAPs), and free fluid appearance. DISCUSSION AND CONCLUSION: As a result, we obtained detailed information in determining intestinal involvement, the length of the affected intestine segment and mesenteric involvement with contrasted abdominal CT. Assuming that the cecum and right colon are affected in almost all cases, we found that additionally terminal ileum involvement is more likely to affect the prognosis than the additional left colon involvement.